12^87divided12^25

5 answers

To divide two exponents with the same base, subtract the exponent in the denominator from the exponent in the numerator.

Therefore, 12^87 ÷ 12^25 = 12^(87-25) = 12^62.
Apply the Zero Power Rule to create an equivalent expression to 9⋅(−33)0+32(8−270)
According to the zero power rule, any number (except zero) raised to the power of zero equals 1.

So, the expression 9⋅(−33)^0 + 32(8−270) can be simplified as:

9⋅1 + 32(8−270)

= 9 + 32(8−270)

= 9 + 32(-262)

= 9 - 8,384

= -8,375
Apply the Zero Power Rule to create an equivalent expression to 9⋅(−33)0+32(8−27^0)
According to the zero power rule, any number (except zero) raised to the power of zero equals 1.

So, the expression 9⋅(−33)^0 + 32(8−27^0) can be simplified as:

9⋅1 + 32(8−1)

= 9 + 32(7)

= 9 + 224

= 233